Spirituality and the nature of learning beliefs among women in non-formal learning environments - Abdul Wahab, Rohaya; Hamzah, Azimi (Elsevier, 2013)
Generally, studies done on learning beliefs in formal classes had shown to have none or little connections to the elements of spirituality. Learning beliefs has often been defined as socially shared intuitions about the nature of knowledge and the nature of learning, Learning beliefs thus look at the various beliefs a learner has on what learning actually means to him or her. Spirituality on the other hand is generally seen as an individual's perceived sacred experiences and is often connected to religion. However, spirituality as seen from the epistemic Islamic perspective is interpreted as a state of purifying one's soul and reforming the self towards achieving God's blessedness Thus, this research tries to explore and focus on identifying and describing the qualitatively different ways in which Muslim women understand and give meanings to learning in non-formal learning contexts, and their close relationship with spirituality. To uncover the learners’ learning beliefs, the phenomenological method of inquiry was adopted. Data were gathered solely from individual in-depth interviews held with five female adult learners undertaking at least two forms of non-formal religious learning programs. Data analysis revealed five hierarchically arranged themes on learning beliefs ranging from a simple level to a more complex one. Initially starting from the ‘acquiring knowledge and applying’ level, learning is seen to relate further into changes and transformation affecting the heart and worldview, shaping their entire being and existence in this world, their views on life and their relationship with others. These are the dimensions of learning beliefs connected to the elements of spirituality.